Modelling and simulation of inclined fuel transfer machine in prototype fast breeder reactor operator training simulator. (2016) - Sankar, Bindu; Jayanthi, T.; Chakraborty, Jaideep; Seetha, H.; Venkatesan, Adhivaraganatham A.; Madhusoodhanan, K.; Murty, S.a.v. Satya
Indira Gandhi Centre for Atomic Research, Kalpakkam has successfully designed a 500 MWe prototype fast breeder reactor (PFBR). It is a proven fact that the critical factor in ensuring safe and reliable operation of any nuclear power plant is a qualified and well-trained personnel and hence, the need for operator training using a simulator. Fuel handling is one of the most important subsystems in a prototype fast breeder reactor. Ex-vessel subassembly transfer is done using an inclined fuel transfer machine (IFTM) which operates remotely and safely. Using IFTM, fresh fuel assemblies are loaded into the reactor, and spent fuel assemblies get unloaded. This paper deals with modelling and simulation of operations of IFTM in a simulator. Virtual panel models and control logic models were modelled using modelling tools present in the simulator. The process modelling was developed in-house using platform independent C++ code with 3D models.